Mismatch repair protein loss in cutaneous head and neck squamous cell carcinoma. Issue 8 (14th September 2020) - Vasan, Kartik; Anand, Sunaina; Satgunaseelan, Laveniya; Asher, Rebecca; Low, Hubert; Palme, Carsten E.; Lee, Jenny H.; Clark, Jonathan R.; Gupta, Ruta
Abstract: Background: The treatment of advanced cutaneous head and neck cutaneous squamous cell carcinomas (HNcSCC) results in significant morbidity. Recently, immune checkpoint inhibitor treatment has been approved for DNA mismatch repair (MMR) deficient patients in a histology‐agnostic manner. This study aims to evaluate the incidence of MMR deficiency in advanced HNcSCC and its association with clinicopathologic factors. Methods: The cohort included 176 consecutive HNcSCC cases treated with curative intent. Immunohistochemistry for MMR proteins (hMLH1, hMSH2, hMSH6, and hPMS2) was performed. Clinicopathological and survival data was collected prospectively. Results: The incidence of MMR protein deficiency was 9.1%. There was no association between age, incidence of metachronous malignancies, clinicopathological factors, or survival outcomes. Conclusion: A higher incidence of MMR deficiency was observed in this cohort of advanced HNcSCC. The lack of association with young age at onset or increased incidence of metachronous malignancies suggests that MMR deficiency is likely to be sporadic in HNcSCC.